Fibrosarcomatous dermatofibrosarcoma protuberans from scar following trauma - Sang Wook Lee; Araya Zaesim; Amanda Jackson; Michael Borkat (University of São Paulo, 2018)
Dermatofibrosarcoma protuberans (DFSP) is an uncommon soft tissue neoplasm of low metastatic potential notable for its progressive growth and high rate of local recurrence after surgical excision. Fibrosarcomatous transformation of DFSP (FS-DFSP) is a rare variant characterized by higher rates of local recurrence and metastasis. Trauma has been hypothesized as a potential risk factor for the development of DFSP, although clear evidence has been lacking. In this study, we report a case of FS-DFSP that was found arising from a previously stable scar following a traumatic injury. A 49-year-old male was diagnosed with keloid scars following a motor vehicle accident where he sustained trauma. 12 years later, a large tumor developed immediately after a second traumatic event to the primary scar. Pathology of the excisional biopsy specimen demonstrated FS-DFSP with focal areas consistent with keloid and hypertrophic scar. This observation demonstrates the development of DFSP from underlying scar following a clear history of trauma. Furthermore, it suggests trauma as a possible trigger for the fibrosarcomatous transformation of DFSP.